A Study on Impact of FDI Flows on Poverty Reduction in India - Dhamija, Reema; Singh, Kalpana (Prabandhan: Indian Journal of Management, 2018)
A key element for successful economic growth in the developing countries is foreign direct investment (FDI) due to the fact that it makes possible the fast and effective transfer and adoption of â€œbest practicesâ€ across the national boundaries. Foreign direct investment also translates into large-scale growth, including the improvement of human capital. Considering growth to be one of the most important factors for causing a reduction in poverty, FDI is critical to achieve this goal. Keeping in view this fact, the present paper investigated the relationship between FDI inflows and poverty reduction in India during the time period from 1990 - 2013. This study employed ARDL (auto regressive distributed lag) approach to study the relationship between the two variables. To measure the extent of poverty reduction in the country, the study used HDI index as a welfare proxy due to limited data available on poverty headcount in India. The independent and control variables considered in the study included net FDI inflows as a percentage of GDP, general government final consumption expenditure as % of GDP, education measured by school enrollment ratio, and inflation. The results of this study revealed that there existed a short-run positive relationship between FDI inflows and poverty reduction in India, that is, the increase in the FDI inflows led to an increase in the HDI, which means an increase in the welfare of the poor, hence resulting in poverty reduction. However, the findings of the study indicated the non-existence of a long run relationship between the FDI inflows and poverty reduction in India.